A phase 1, open-label study to determine safety and tolerability of the topical application of mesenchymal stem/stromal cell (MSC) exosome ointment to treat psoriasis in healthy volunteers - Chandran, Nisha Suyien; Bhupendrabhai, Monil Nagad; Tan, Thong Teck; Zhang, Bin; Lim, Sai Kiang; Choo, Andre Boon Hwa; Lai, Ruenn Chai (Cytotherapy (Oxford, England), 2025)
Topical application of mesenchymal stem/stromal cell (MSC) exosomes have yielded encouraging results in the treatment of psoriasis in pre-clinical studies. The safety of topical applications of MSC exosome in ointment has not yet been determined in human subjects. To assess the safety and tolerability of an MSC exosome ointment, PTD2021P, for topical application in healthy adult volunteers. Ten healthy adult volunteers were enrolled. All subjects received topical treatment with PTD2021P immediately followed by Vesiderm liposome cream ter in die (TID) (thrice a day) on the forearm with a gap of 4 hours between doses for 20 days and underwent another round of screening procedure at end of study (Day 21 + 3 days). Screening procedures included vital signs, blood examinations, photographs and visual assessment of the area of application. All through the treatment period, the subjects completed the daily Subject Diary to capture adverse events, concomitant medications, and time of study product application. One subject was reported with 1 treatment-emergent adverse event (TEAE) of COVID-19 infection during the study. The TEAE was moderate in severity and unlikely related to the study drug. This TEAE was resolved and the subject recovered fully. No subject was reported with clinically significant abnormality for laboratory parameters. As per the visual assessment of the area of application, no subject had dryness, itch, oozing/crusting, redness, scratch marks, skin thickening, sleeplessness, or swelling at the area of application of skin. PTD 2021P was well tolerated for topical application. There were no serious adverse events (SAEs) or TEAEs related to the treatment, and no subject discontinued the study. No clinically significant abnormality was reported for laboratory parameters and vital signs. No abnormality was reported for visual assessment of the area of application of exosome ointment. This ointment could be an alternative therapeutic option for patients who are refractory to current first line therapy.